Gender, metacognition, and vocabulary learning strategies of Malay ESL learners - Engku Ibrahim, Engku Haliza; Sarudin, Isarji; Muhamad, Ainon Jariah (Institute of Physics Publishing, 2018)
Research has shown that female students are likely to be more successful in language learning when compared to male students due to the differences in their metacognitive learning strategies1. This study aims to investigate if there are differences in metacognition, vocabulary learning strategies and the vocabulary size between male and female students. The instruments utilised study were a Vocabulary Learning Strategy Questionnaire2 and the Vocabulary Levels Test3. 113 pre-university ESL learners participated in this study. A quantitative research design was employed. Findings of this study showed that there is no significant difference between the vocabulary size and metacognitive learning strategies used by male and female students. A better understanding of metacognitive strategies, vocabulary size and gender will enhance teachers’ and learners’ awareness of the use of the said strategies for a more effective vocabulary acquisition. The findings provide beneficial pedagogical implications relevant not only to language instructors but also educators and researchers alike.